Cereal bars functionalized through Bifidobacterium animalis subsp. lactis BB-12 and inulin incorporated in edible coatings of whey protein isolate or alginate. Issue 10 (7th October 2019) - Pereira, Joana Odila; Soares, José; Monteiro, Maria J. P.; Amaro, Ana; Gomes, Ana; Pintado, Manuela
Abstract : Currently, cereal bars are gaining interest globally because of their nutritionally balanced and convenient nature. Abstract : Currently, cereal bars are gaining interest globally because of their nutritionally balanced and convenient nature. One healthy strategy is to add probiotics to cereal bars, to make them a functional food product. So, in this study a cereal bar functionalized with edible coatings of whey protein isolate (WPI) and alginate (ALG) incorporated with Bifidobacterium animalis subsp. lactis BB-12 and inulin was developed and evaluated for its consumer acceptability and physicochemical and microbiological properties, throughout 90 days of storage. WPI-coated cereal bars were shown to be the solution that better maintained the level of the incorporated probiotic strain when compared to the ones coated with ALG, throughout storage and throughout in vitro gastrointestinal digestion. The physicochemical properties of the bars, namely a w, moisture content, color and texture, were not altered during the storage period. The sensory evaluation showed that coated bars were accepted as well as control bars. Moreover, the consumers appreciated better the odor and flavor of WPI-coated bars than those of ALG-coated bars.